198 A Team-based Approach to an Integrated Model of Diabetes Care. (April 2022) - Croisant, Sharon; Bohn, Krista; Prochaska, John; Sallam, Hanaa; Serag, Hani; Urban, Randall
Abstract : OBJECTIVES/GOALS: Diabetes is related to risk for heart disease, stroke, high blood pressure, and COVID-19. It is exacerbated by built/social environment issues, e.g., food insecurity, access to healthy foods and health care, and other poverty-related factors. Our goal is to assess the efficacy of an integrated care model for patients with poorly controlled diabetes. METHODS/STUDY POPULATION: We utilize an integrated, team-based approach to diabetes treatment. In a traditional care model, too little focus is on social determinants and their impacts on health and well-being. Our project involves enrollment of patients with diabetes in an intervention whereby their medical care is integrated with intensive diabetes education and provision of social and other health services, including diet and nutrition, exercise, provision of foods and nutritional supplements, and other support services as needed to achieve optimal health and to reduce morbidity and unnecessary hospitalization and emergency room visits. Subjects are underserved patients treated through our non-profit community clinic partners. We track metrics including individual outcomes, organizational outcomes, and collective impact. RESULTS/ANTICIPATED RESULTS: We anticipate that patients enrolled in this study will demonstrate significant improvements in diabetes control and management. Clinical improvements will include better glycemic control, improved hypertension and dyslipidemia management, reduced complications, and increased preventive measures including foot, eye and oral health exams and monitoring of microalbuminuria. Overall, we anticipate decreased frequency of hospitalizations and readmissions as well as decreased frequency of emergency care visits for treatment of diabetes-related issues. We expect patients to experience enhanced self-efficacy, increased physical activity, and improved quality of life. Their outcomes will be compared to controls receiving the standard medical regimen, matched on age, race, gender, and time of onset. DISCUSSION/SIGNIFICANCE: These activities will improve understanding of factors influencing diabetes outcomes at individual and upstream levels. It will inform food distribution and models of care for improved patient outcomes, including social determinants of health and will establish new protocols for community-based provision of health care to our most vulnerable.